AC fault ride-through coordinated control strategy of LCC-MMC hybrid DC transmission system connected to passive networks. (October 2021) - Xin, Yechun; Lou, Weitao; Li, Guoqing; Jiang, Shouqi; Wang, Tuo; Yang, Yong
Highlights: By reducing the number of inserted submodules in each phase arm, the DC voltage at inverter side can be decreased quickly and the transmission of DC power can be restored. A method is proposed to determine adjusted value of DC voltage at inverter side according to the drop degree of AC bus voltage at sending end. By reducing AC components of the arm voltage, the load can actively participate in regulating the unbalanced power of converter station. The control strategy can be applied to passive networks with high requirements for AC characteristics by ensuring good power quality at receiving end. Abstract: The LCC-MMC hybrid DC transmission system can combine the economic advantages of LCC and the technical advantages of MMC, and has broad application prospects for supplying power to passive networks. In order to solve the problem of interruption of DC power transmission caused by AC fault at sending end, a fault ride-through coordinated control strategy based on controlling MMC arm voltage is proposed. The discharge mechanism of submodule capacitor and AC fault characteristics are analyzed by establishing the mathematical model of LCC-MMC hybrid DC transmission system. A control strategy for adjusting the AC and DC components of MMC arm voltage is designed. The DC power transmission can be maintained by reducing DC component of the arm voltage, and load can actively adjust the unbalanced power of converter station by reducing AC component of the arm voltage. The principles for parameters selection are proposed according to different severity of AC fault and the regulation limit of AC component is set according to the characteristics of passive networks. The control strategy can make the load and MMC work together to maintain safe and stable operation of the system. Finally, the effectiveness of proposed coordinated control strategy is verified by simulation results for AC fault of different severity.